Avian responses to an emergent, wetland weed. (29th November 2016) - Carlos, Emma H.; Weston, Michael A.; Gibson, Maria
Abstract: African boxthorn ( Lycium ferocissimum Solanaceae) is a Weed of National Significance in Australia. It is particularly problematic in Victoria and is thought to not only threaten native wildlife but also provide important habitat, particularly to birds, when there is no native alternative. In a wetland ecosystem such as a saltmarsh, boxthorn has the potential to increase structural complexity because it can stand as an emergent above surrounding vegetation. We compared bird assemblages and behaviour in saltmarsh vegetation with and without boxthorn in a coastal wetland in south‐east Australia. Species assemblage, but not richness, changed with the presence of boxthorn. The presence of singing honeyeaters ( Lichenostomus virescens ) and white‐fronted chats ( Epthianura albifrons ), the two most common native bird species (based on numerical and spatial dominance), appeared to drive these differences; singing honeyeaters preferred boxthorn while white‐fronted chats avoided it. The presence of boxthorn increased the seasonal availability of fruit and flowers, which was reflected by a high frequency of foraging for fruit and nectar where boxthorn was present. In saltmarshes without boxthorn, there was a higher frequency of foraging for insects. Some, but not all, species responded to increased structural complexity and fruit/floral resources provided by boxthorn. Consequently, management by reducing boxthorn is likely to alter bird communities and the usage of sites by some native species, thus management success should consider fine‐scale biodiversity objectives, such as managing for particular types or species of birds.